2021
DOI: 10.1101/2021.03.10.21253079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns of respiratory Gram-negative bacterial isolates from COVID-19 patients in Switzerland

Abstract: Background Bacterial superinfections associated with COVID-19 are common in ventilated ICU patients and impact morbidity and lethality. However, the contribution of antimicrobial resistance to the manifestation of bacterial infections in these patients has yet to be elucidated. Methods We collected 70 Gram-negative bacterial strains, isolated from the lower respiratory tract of ventilated COVID-19 patients in Zurich, Switzerland between March and May 2020. Species identification was performed using MALDI-TO… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Unlikely, a study conducted in Switzerland 15 isolated Pseudomonas aeruginosa (46%) as most common isolate. 15 Similarly, a study from Germany and Iran revealed the Klebsiella spp (47.82% & 25.59%) were the most common isolated gram negative bacteria from the samples of COVID-19 patient which is also in accordance to our study. 19,20 This discrepancy may be due to the fact that difference in geographical location might be a factor of different bacterial pathogen isolation.…”
Section: Covid-19supporting
confidence: 91%
See 2 more Smart Citations
“…Unlikely, a study conducted in Switzerland 15 isolated Pseudomonas aeruginosa (46%) as most common isolate. 15 Similarly, a study from Germany and Iran revealed the Klebsiella spp (47.82% & 25.59%) were the most common isolated gram negative bacteria from the samples of COVID-19 patient which is also in accordance to our study. 19,20 This discrepancy may be due to the fact that difference in geographical location might be a factor of different bacterial pathogen isolation.…”
Section: Covid-19supporting
confidence: 91%
“…21 Majority of the gram negative isolates were resistant to ampicillin, amoxicillin + clavulanic acid, ceftriaxone, piperacillin + tazobactam and the same has been documented by the studies done Gysin et al,. 15 They reported that piperacillin/tazobactam (65.6%), cefepime (56.3%), ceftazidime (46.9%) and meropenem (50.0%) were resistant drugs against gram negative isolated from COVID-19 patients. In our study, aminoglycoside and colistin was the most sensitive drugs against the isolated gram negative isolates which is in accordance with the study conducted by Gysin et al 15 , Sharifipour et al, 18 and Mahmoudi et al, 20 Moreover, studies conducted by Mahmoudi et al, 20 and Sharifipour et al, 18 reported that vancomycin is most effective antibiotic against MSSA and MRSA which is accordance to our study.…”
Section: Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that E. coli, K. Pneumoniae, and Pseudomonas spp. were the most commonly isolated bacteria, while Marina G et al [17] reported that Pseudomonas aeruginosa and Enterobacterales were the most prevalent in their study. The isolation of organisms is being influenced by the geographical region.…”
Section: Plos Global Public Healthmentioning
confidence: 77%
“…Cusumano et al [163] particularly find that Staphylococcus aureus bacteremia may be an important predictor of worse outcome. There is an increasing antibiotic resistance profile with co-infection [122,123,127,135,137,140,142,144,146,157,159,160,163,164]. For example, some American centers have been particularly inundated with multi-resistant coliforms [135,157].…”
Section: The Impact Of Covid-19 On Associated Post-onset Bacterial Infectionsmentioning
confidence: 99%